A model of ICT acceptance by academics : a case in Sindh Province, Pakistan - Chandio, Shahmurad
The use of Information and Communication Technology (ICT) in education sector has altered the way teaching and learning activities conducted in all levels. Despite the rapid growth of ICT adoption in developed countries, a number of challenges have hindered the use of ICT in developing countries. Since, the ICT have massive potential and is considered as enabler for social economic development of a country. Therefore, developing countries needs to adopt ICT, in order to achieve the sustainable development and quality of life. Hence, such a motivation towards technology have compelled every country to produced ICT trained people. Driven by this, higher education institutions (HEIs) around the world are integrating ICT tools and adopting latest technologies to continue providing quality education. In fact, the effectiveness of any modern ICT technology depends upon the acceptance and utilization by academics in any academic institutions. However, literature shows that, in past research on ICT is focused in context of industrial sector, e- governance, e-commerce and education in general. While it is believed that, success of education system depends upon academics. It was found that there were rare studies on ICT acceptance by academics especially in context of developing countries. This study addressed this gap and identified factors that influences the acceptance of ICT by academics. Subsequently, this study aimed to develop a model of ICT acceptance by academics. The study was carried out by adopting mix methods approach. The data was collected using survey questionnaire, followed by face-to-face interviews from academics. The 325 valid responses, were analysed using SPSS-SEM methods that yields and test measurement and structural models. Followed by interviews data, using thematic analysis method. The study has successfully explored the success factors for ICT acceptance by academics and the findings show that the proposed model achieved an acceptable fit with the data. The results revealed that the Culture, External Incentives, Perceived Needs, Job Relevance, Performance Expectancy, Effort Expectancy and Facilitating Conditions were found to have significant effect on intention to use ICT. In contrast, Social Influence had no significant effect on intention to use ICT. Further, findings provide the guidance towards the ICT management and utilization in HEIs. This study also suggests that academics should be provided with be regular trainings relevant to ICT services. The impact of this research work will be on higher education to improve the quality of the education system by effectively utilizing ICT in HEIs.